Rosalvo Florentino de Souza um intelectual a serviço do magistério na imprensa paulista (1949 a 1957) - Bastos, Francisco Glauco Gomes (Editora Oficina Universitária, 2022)
"Stating that Rosalvo Florentino de Souza is an intellectual at the service of education may seem strange, since, even though he wrote for two decades in the newspaper A Gazeta, from 1949 to 1968, according to the collection of clippings that were at the Instituto of Educational Studies "Sud Mennucci", on themes related to education, even having participated as a member and as founder of several class entities linked to education, even having been a secondary teacher, is not found in the literature on the History of Education, either in Brazil , whether from the State of São Paulo, any reference to it. It was from a survey carried out by an undergraduate student on certain newspaper clippings left by him at the Institute of Educational Studies "Sud Mennucci", that, through professor and researcher Rosa Fátima de Souza Chaloba, I became aware of the legacy left by this Bahian born in Caetité". There is hard work, serious research and devotion to education and teaching in this thesis book. Professor Glauco Bastos brings, through an immersion in time-worn documents, an intellectual look - Rosalvo Florentino de Souza - on the school culture of the 1940s to 1960s. the History of Brazilian Education and, even more, to fill invaluable gaps in public education policies in São Paulo at the time studied. Through a work based on Sherlock Holmes, Glauco Bastos brilliantly appropriates articles written by columnist Rosalvo Florentino in the newspaper "A Gazeta" to present us with an extraordinary piece for understanding the many paths taken by the national teaching profession up to the present day. Finally, academia and the general public find this book a unique source of research and the certainty of a fruitful and enjoyable reading.